PELAYANAN KONSULTASI ADAT/BUDAYA BALI “BALI SHANTI” UNIVERSITAS UDAYANA - Astariyani Astariyani; N. L. G., I K. Sardiana; W. P. Windia (Buletin Udayana Mengabdi, 2010)
ABSTRACT The present community service aimed to give consultation in order to solve of many problems related to Balinese customs and culture. The activity of community service was conducted on Bali Shanti office, located at Graduate school of Udayana University building, Denpasar. It can be concluded that the responses of Bali’s society were positive to the service. The consultation activity were attended by 102 participants during 2009. The origin of the participants were from Bali 80 percent, other places in Indonesia 15 percent, and expatriat 5 percent. The problem discussed in the consultation activity were among others family problem 60 percent, village customs legal drafting (awig-awig desa adat) 25 percent, culture 10 percent, and 5 percent others.